Anomalous Josephson effect modulated by magnetic misorientation in a topological unconventional superconductor hybrid structure. (29th December 2021) - Liu, Tingmin; Zhou, Linyi; Tao, Y. C.
Abstract: We study the anomalous Josephson effect induced by magnetic misorientation of asymmetric s -wave superconductor (SC)/ferromagnet insulator (FI)/normal layer/FI/ d -wave SC junctions on a surface of topological insulator (TI). For the out-of-plane case, the magnetic misorientation not only leads to anomalous Josephson effects, but also realizes state transitions. However, for the in-plane case, the state transitions do not turn up any more. In particular, the plateaus phenomenon for d xy -wave SC junction emerges all the time. In addition, in the context of the in-plane case, the supercurrent rectification can be modulated by the magnetic misorientation. These unique phenomena can be employed to identify different d -wave superconductivities of three-dimensional TI and manufacture the supercurrent devices with such functions as phase storing, rectification, and quantum computation.